Nanotechnology in Medical Physics: Innovations and Applications - Dakhil, Ruaa Nadheer; Al-Mustaqbal, Ameer Saad Hasan; MALIK, MURTADHA MAHDI; Kamil, Ahmed Mohammed; Nawaf, Qais Hisham (American Journal of Biodiversity, 2025)
Nanotechnology is assertively presented as a transformative force in modern medicine, being considered revolutionary and innovative in terms of therapeutics, diagnostics, and imaging. The many commercial applications of nanotechnology to develop medical applications boasting nearly infinite prospective benefits can lead to pollution and risky exposures. This development emphasizes the other side of the coin inherent to revolutions and new technologies. Fundamental insights and existing boundaries that necessarily slow the speedy evolution of a research field are beyond initial enthusiasts of the revolution. Possible ethical, social, economic, and environmental challenges as barriers are discussed regarding the new revolution in nanobiotechnology, which still engenders a profusion of publications and public funding devoted to biomedical matters. The explicitly essay objectives are (i) to overview the key applications and implications of nanotechnology for medical purposes and (ii) to discuss extant and emerging disputes concerning this ongoing revolution in medicine and other bio-related activities, with a special emphasis on smart and multifunctional nanoparticles. Five years ago. This investigational work prompted an extended and vibrant debate that provided an open forum on the barriers to the flourishing and recommended investments in nanoscience and nanotechnology. Hampering the steadily incorporation of nanotechnologies has been a high priority for several countries ever since.